2006
DOI: 10.1002/jmr.771
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approaches for prediction of linear B‐cell epitopes on proteins

Abstract: Identification and characterization of antigenic determinants on proteins has received considerable attention utilizing both, experimental as well as computational methods. For computational routines mostly structural as well as physicochemical parameters have been utilized for predicting the antigenic propensity of protein sites. However, the performance of computational routines has been low when compared to experimental alternatives. Here we describe the construction of machine learning based classifiers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 19 publications
0
85
0
Order By: Relevance
“…Previous methods for predicting linear B-cell epitopes (e.g., 15,17,19,18,20 ) have been evaluated on datasets of unique epitopes without applying any homology reduction procedure as a pre-processing step on the data. We showed that performance estimates reported on the basis of such datasets is considerably over-optimistic compared to performance estimates obtained using the homology-reduced datasets.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous methods for predicting linear B-cell epitopes (e.g., 15,17,19,18,20 ) have been evaluated on datasets of unique epitopes without applying any homology reduction procedure as a pre-processing step on the data. We showed that performance estimates reported on the basis of such datasets is considerably over-optimistic compared to performance estimates obtained using the homology-reduced datasets.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Input sequence windows ranging from 10 to 20 amino acids, were tested and the best performance, 66% accuracy, was obtained using a recurrent neural network trained on peptides 16 amino acids in length. In the method of Söllner and Mayer 19 , each epitope is represented using a set of 1487 features extracted from a variety of propensity scales, neighborhood matrices, and respective probability and likelihood values. Of two machine learning methods tested, decision trees and a nearest-neighbor method combined with feature selection, the latter was reported to attain an accuracy of 72% on a data set of 1211 B-cell epitopes and 1211 non-epitopes, using a 5-fold cross validation test 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as shown by Blythe and Flower [5], the performance of such methods is only marginally better than that of random guessing. Hence, several methods based on machine learning and statistical approaches have been recently proposed for predicting linear B-cell epitopes [18,30,32,8,31,10,9].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that better methods or new amino acid indices are needed for B cell epitope prediction. New methods such as neural networks, hidden Markov models and support vector machines have been applied to B cell epitope prediction very recently [25,[35][36][37]. However, the performance improvements are still limited.…”
Section: Relative Connectivity Can Be a Good Choice For B Cell Epitopmentioning
confidence: 99%